Workspace optimisation of 3R manipulator - a multi-objective approach. (13th August 2019) - Panda, S.; Mishra, D.; Biswal, B.B.
Optimum workspace with a compact manipulator is one of the decisive factors in the optimum design of robot manipulator. In this article the workspace volume of a 3R robot manipulator has been optimised on a multi-objective basis using differential evolution (DE) algorithm. An additional objective of this study is to synthesise the total void cross-section area. The proposed algorithm is tested on four diverse examples. The result obtained are compared with the results available in the literature. The key design kinematic parameters are identified through a statistical analysis. To ensure the practical applicability the proposed design approach has been tested on two industrial manipulators viz. KUKA KR-30 and Mitsubishi MRP-700A. Furthermore, it has been found that the predicted results of the simulation are in excellent agreement with the actual values.